2014
DOI: 10.4251/wjgo.v6.i12.438
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant chemoradiotherapy for locally advanced rectal cancer: The debate continues

Abstract: Rectal carcinoma represents the 30% of all colorectal cancers, with about 40000 new cases/years. In the past two decades, the management of rectal cancer has made important progress, highlighting the main role of a multimodality strategy approach, combining surgery, radiation therapy and chemotherapy. Nowadays, surgery remains the primary treatment and neoadjuvant chemoradiotherapy, based on fluoropyrimidine (5-FU) continuous infusion, is considered the standard in locally advanced rectal carcinoma. The aim is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…A total of 171 studies were identified in the database searches, and 10 full text articles were reviewed after exclusion of 161 for not meeting the inclusion/exclusion criteria. Two studies were subsequently excluded on the basis of being a review 4 or a protocol. 18 Eight studies were included in the final meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 171 studies were identified in the database searches, and 10 full text articles were reviewed after exclusion of 161 for not meeting the inclusion/exclusion criteria. Two studies were subsequently excluded on the basis of being a review 4 or a protocol. 18 Eight studies were included in the final meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“… 3 Thus, interest has grown in neo-adjuvant (preoperative) therapy for pancreatic cancer. In advanced rectal cancer, neo-adjuvant therapy is considered the standard of care, 4 and neo-adjuvant therapy in patients with resectable pancreatic cancer has yielded some encouraging results. 5 11 The proposed benefits of chemoradiotherapy (CRT) in pancreatic cancer are control of local disease and the improved rate of complete resection.…”
Section: Introductionmentioning
confidence: 99%
“…Radiotherapy (RT) was delivered with a 3D-conformational multiple field technique at a dose of 45 Gy (1,8 Gy/fraction) to the whole pelvis plus a 5,4–9 Gy (1,8 Gy/fraction) to the tumor volume. Chemotherapy (CHT) consisted of weekly OXP (50 mg/m 2 , day 1) and five daily continuous infusions of 5-FU (200 mg/m 2 /day) of each week of RT, based on promising results in high rate of pCR [78]. Surgery was planned 7–9 weeks after the end of nCRT and its type was left to surgeon's discretion.…”
Section: Methodsmentioning
confidence: 99%
“…Neoadjuvant therapy has also led to the increase of number of conservative interventions, as well as improving the prognosis by reducing the incidence of recurrence and increasing survival [1, 2, 3, 4, 5, 6]. On the other hand surgery alone has a high rate of complications (10-65%) and local recurrence (10-29%) [7].…”
Section: Introductionmentioning
confidence: 99%